PSYCHOLOGICAL FACTORS AFFECTING STUDENTS’ SPEAKING PERFORMANCE OF THIRD SEMESTER STUDENTS AT ENGLISH STUDY PROGRAM OF STKIP INSAN MADANI AIR MOLEK - Syaftinentias, Widi; Wirawan, Fajar; Novita, Loly; Masran, Silviana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The objective of the research is to find out the psychological factors affect students’ speaking performance The research is descriptive qualitative research. The participant of this research was taken through random sampling technique. The participant of this class is class A which consist of 47 students. The research instrument of this research is questionnaire. In this research, the technique analysis data are collecting data, categorized the data based on indicators, describe the data and make conclusion. Based on the result of the research e, there are several psychological factors which become the barriers for the students n performing their speaking, they are anxiety, fear of making mistakes, shyness, lack of motivation, and lack of confidence. These psychological factors not only appear from one student who is presenting his speaking competence in front of the class, but also from other students who act as audience in individual speaking activity.Keywords: psychological factors, speaking performance